Brazilian scientific production about travestility and transsexuality: from disease to resistance (Terr@ Plural, 2020)
The main goal of this article is to evidence the Brazilian scientific production from the published researches in the Thesis Catalog of dissertations from CAPES, about transvestites and transsexuals. Therefore, in a universe of more than a million academic researches published until April 2019, it is evidenced a total of only 573 papers related to the theme, representing 0,05 of the total productions. Even with the verified increase of the publishes from the year 2008, these numbers still not represent the little representativity of the research area, pointing to the marginalization of these studies, in the scientific Brazilian production scenario. However, in this article, we evidence the emergency of other themes, such as body, transphobia, health, gender studies, indicating that the perspective if the diseases have been undermined towards the resistance perspective, while the reflections around the promotion of the citizenship of these people have won emphasis in the researches.
Keywords: Gender; Transvestite; Transexuals; Scientific Journals